Patent Law: Decisions of the Supreme Court of India (Journal of Intellectual Property Rights (JIPR), 2023)
This Paper seeks to examine the theoretical underpinnings of The Patents Act, 1970 (Patents Act), as constructed bythe Supreme Court of India (Supreme Court) in the last 71 years. An analysis of decisions of the Supreme Court revealsthat: (i) in none of the cases, validity of The Patents Act was challenged; (ii) unlike the decisions on copyright anddesign laws where the Court invoked both Labour and Utilitarian frameworks as supplementary and complimentary to eachother to justify the ‘why’ of two distinct copyrights envisaged by The Copyright Act, 1957 and The Designs Act, 2000,the Court in patent cases has used only Utilitarian Theory; (iii) Court has not ignored Natural Right and Labour theories asin its opinion Natural Right justification is only a means to achieve the end of social good; (iv) in the opinion of the Court,both ‘sense’ and ‘nonsense’ of Bentham may coexist as means and end; and (v) protection of patent rewards labour put in bythe inventor and in exchange provides invention and knowledge to the society. Paper argues that the Court should haveapplied judicially manageable standards to rigorously scrutinize the theoretical underpinnings of Patent Law from allpossible angles.